3D-printed synthetic tissues - Booth, MJ; Bayley, H (Portland Press, 2016)
'Bottom-up' approaches in synthetic biology have been used to construct synthetic cells from simple biological components. By contrast, relatively little work has been done on synthetic tissues in which collections of cells cooperate to achieve functionality that cannot be generated by individual compartments. We have developed a 3D printer, which can create structures containing hundreds or thousands of communicating aqueous droplets arranged in programmed patterns. These tissue-like materials can adopt properties such as the ability to fold or conduct electrical signals. Furthermore, the properties of the materials can be extended, so that they become true synthetic tissues through the performance of sophisticated functions such as protein synthesis. In addition, we have shown that 3D-printed synthetic tissues can be controlled and energized externally, for example by light. Printed synthetic tissues might find a variety of uses in medicine and could even be interfaced directly with living tissues. As they contain no genome and cannot replicate, synthetic tissues are comparatively safe for medical applications.